Influence of Surface Roughness, Nanostructure, and Wetting on Bacterial Adhesion - Mu, Minchen; Liu, Shuhao; DeFlorio, William; Hao, Li; Wang, Xunhao; Salazar, Karla Solis; Taylor, Matthew; Castillo, Alejandro; Cisneros-Zevallos, Luis; Oh, Jun Kyun; Min, Younjin; Akbulut, Mustafa (Langmuir, 2023)
Bacterial fouling is a persistent problem causing the deterioration and failure of functional surfaces for industrial equipment/components; numerous human, animal, and plant infections/diseases; and energy waste due to the inefficiencies at internal and external geometries of transport systems. This work gains new insights into the effect of surface roughness on bacterial fouling by systematically studying bacterial adhesion on model hydrophobic (methyl-terminated) surfaces with roughness scales spanning from ∼2 nm to ∼390 nm. Additionally, a surface energy integration framework is developed to elucidate the role of surface roughness on the energetics of bacteria and substrate interactions. For a given bacteria type and surface chemistry; the extent of bacterial fouling was found to demonstrate up to a 75-fold variation with surface roughness. For the cases showing hydrophobic wetting behavior, both increased effective surface area with increasing roughness and decreased activation energy with increased surface roughness was concluded to enhance the extent of bacterial adhesion. For the cases of superhydrophobic surfaces, the combination of factors including (i) the surpassing of Laplace pressure force of interstitial air over bacterial adhesive force, (ii) the reduced effective substrate area for bacteria wall due to air gaps to have direct/solid contact, and (iii) the reduction of attractive van der Waals force that holds adhering bacteria on the substrate were summarized to weaken the bacterial adhesion. Overall, this study is significant in the context of designing antifouling coatings and systems as well as explaining variations in bacterial contamination and biofilm formation processes on functional surfaces.